Determinants of successful exclusive breastfeeding on primiparas mothers - Dian Shofiya; Sri Sumarmi; Agus Sulistyono; Bagong Suyanto (AOSIS, 2023)
Background: Since 2016 the City of Surabaya has assisted for the first 1000 days of an infant's life. The given mentoring aimed to reduce stunting and increase exclusive breastfeeding (EB) coverage. However, EB coverage has yet to be achieved. Objective. This study aimed to determine the effects of delayed onset of lactation, early initiation breastfeeding (EIBF), and frequency of antenatal care on exclusive breastfeeding in primipara mothers. Methods: The research design was cross-sectional, the number of samples was 131 out of 378 primipara mothers and lactating pregnant women selected by cluster random sampling. Chi-square and logistic regression analysis α=0.05. data was collected in April 2021. Results: The results showed that exclusive breastfeeding was associated with the onset of lactation and early initiation of breastfeeding (p-value = 0.022 and p-value = 0.014). EIBF and timely onset lactation had a greater chance of successful EB. Conclusion: EB and the timely onset of lactation are likely to determine the success of EB. Therefore, EIBF and lactation onset are enhanced for EB success.